KONSOLIDASI GERAKAN ANTI KORUPSI BERBASIS AKADEMISI MELALUI JURNAL INTEGRITAS DAN ACS 2018 - Marta, Rustono Farady (Jurnal Pengabdian dan Kewirausahaan, 2019)
Corruption is the most latent crime, because it is pattern tends to be collective and is massive. Now the complexity and level has reached a worrying stage, so it needs the attention of various parties to deal with it. In addition to the Corruption Eradication Commission (KPK), of course the participation of interdisciplinary academician needs to contribute quality thinking to provide solutions to one of the major problems in Indonesia. Therefore, the KPK took the initiative to organize the dissemination of selected research results in the Jurnal Integritas in a scientific seminar while supporting the implementation of The 3rd Anti-Corruption Summit or abbreviated as ACS 2018 in Makassar. This is intended as a strategic step in consolidating the anti-corruption movement based on academician. Keywords:  Academician, ACS 2018, Corruption Eradication, Jurnal Integritas